ENHANCING STUDENTS’ LEARNING OUTCOME IN SPORT CLASS THROUGH STUDENT FACILITATOR AND EXPLAINING (SFE) TEACHING MODEL - Aprizal Aprizal (Ta'dib, 2017)
An ineffective teaching strategy might have some drawbacks such as students’ passiveness and  lack of opportunities to exercise that cause the students difficult to comprehend rythmic gymnastic movement in Sport class. To improve the condition, the researcher conducts a Classroom Action Research (CAR) consisting of four stages; planning, acting, observing, and reflecting, by  implementing a Student Facilitator and Explaining (SFE) teaching model which facilitates the students more chance to learn with peers. The subject of the research was the fourth grade of elementary school students of SDN 23 Koto Gadang Hilir Kecamatan Padang Ganting, Tanah Datar regency, academic year 2016/2017. The instruments of the research were both observation sheet and test. Cycle 1 result shows both the test result: 67% of psycomotoric and 71% cognitive aspects were successfully achieved, and  the observasion result showing 83% of the teacher SFE activities  and 77% students were active. Meanwhile, in Cycle 2, it is found that the students’ psycomotor was increased to 88% and their cognition 93%. The teacher’s SFE activities were improved to 94% and 95% of the students were active. The results indicate that SFE teaching model could enhance the students’ learning outcome in Sport class particularly on senam irama subject taught at the fourth grade of SDN 23 Koto Gadang Hilir Kecamatan Padang Ganting Tanah Datar regency.